2019
DOI: 10.1186/s12933-019-0937-7
|View full text |Cite
|
Sign up to set email alerts
|

Greater glucagon-like peptide-1 responses to oral glucose are associated with lower central and peripheral blood pressures

Abstract: Background and aim: Cardiovascular diseases (CVDs) are globally the leading cause of death and hypertension is a significant risk factor. Treatment with glucagon-like peptide-1 (GLP-1) receptor agonists has been associated with decreases in blood pressure and CVD risk. Our aim was to investigate the association between endogenous GLP-1 responses to oral glucose and peripheral and central haemodynamic measures in a population at risk of diabetes and CVD. Methods: This cross-sectional study included 837 Danish i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Moreover, a good fit was obtained between the observed relationship and the theoretically constructed model. The exposure-response relationship of GLP-1 was also demonstrated in a cross-sectional study, and linear regression analysis showed that higher glucose-stimulated GLP-1 levels were associated with clinically relevant lower blood pressure (associated with beneficial effects on the cardiovascular system) (35). In addition, a strong relationship was demonstrated between the mean and total drug exposure and MACE HR.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, a good fit was obtained between the observed relationship and the theoretically constructed model. The exposure-response relationship of GLP-1 was also demonstrated in a cross-sectional study, and linear regression analysis showed that higher glucose-stimulated GLP-1 levels were associated with clinically relevant lower blood pressure (associated with beneficial effects on the cardiovascular system) (35). In addition, a strong relationship was demonstrated between the mean and total drug exposure and MACE HR.…”
Section: Discussionmentioning
confidence: 70%
“…In particular, Noyan-Ashraf et al [30] showed, in an experimental model, that liraglutide administration for 7 days before AMI induction reduces infarct size and improves survival by engaging pro-survival pathways in cardiomyocyte. Moreover, chronic treatment with GLP-1 RA has been shown to reduce blood pressure and plasma levels of atherogenic lipoproteins, potentially resulting in a better hemodynamic profile and in a lower coronary atherosclerotic burden when AMI occurs [31][32][33]. Similarly, SGLT-2i administration was found to preserve cardiac contractile function and efficiency during myocardial ischemia-reperfusion injury, and also to improve metabolism and up-regulation of antioxidative proteins after coronary artery ligation in animal models [34].…”
Section: Discussionmentioning
confidence: 99%
“…The GLP-1R is a highly effective target for managing type 2 diabetes by increasing insulin secretion, which lowers blood glucose levels. Enhanced glucose-stimulated GLP-1 responses may have positive impacts on vascular function, reducing the risk of cardiovascular disease and mortality, and lowering central and peripheral blood pressure [ 22 ]. Diabetic patients face an increased risk of developing metabolic syndrome, and in some cases, thoracic adipose tissue secretes higher levels of Cer16:0, which amplifies oxidative stress, systemic inflammation and reduces endothelium-dependent vasodilation, resulting in adverse cardiac outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%